Analisis Yuridis Pertanggungjawaban Korporasi Terhadap Perbuatan Melampaui Baku Mutu Udara Ambien Sebagai Tindak Pidana Lingkungan Hidup - Komang Orba Ambara Yuda; Anak Agung Sagung Laksmi Dewi; I Nyoman Sutama (Jurnal Preferensi Hukum, 2025)
The company's role in advancing the community's economy brings a number of positive impacts, including the growth of deviant behavior carried out by companies with economic motivation, namely environmental pollution. The formulation of the problems in this paper are: How is corporate liability for environmental crimes? and How are criminal sanctions for perpetrators of criminal acts exceeding ambient air quality standards? This research uses a normative legal research approach with a focus on statutory and conceptual analysis. This writing aims to analyze corporate criminal liability for exceeding ambient air quality standards and also criminal sanctions obtained by corporations. The results of this research show that Law Number 32 of 2009 concerning Environmental Protection and Management emphasizes criminal liability for environmental violations. This regulation aims to take action against environmental pollution. Article 98 of the Law regulates criminal sanctions in the form of imprisonment and fines for perpetrators of environmental violations.